Estudio del uso ilegítimo de las marcas en el Ecuador (Periodo 2020 – 2023) - Reyes Navarrete, David Isaías (2024)
The illicit use of trademarks in Ecuador, especially between 2020 and 2023, poses a significant challenge to intellectual property rights, with a specific focus on industrial property and distinctive signs. This issue adversely affects the commercial dynamics and decreases consumer confidence. This research aims to identify the causes and consequences of this practice and to develop legal strategies for its prevention and eradication. It highlights the importance of protecting trademarks, which are fundamental for market integrity. The study was conducted with a qualitative approach, allowing for a detailed analysis of specific cases and relevant legislation at both national and international levels. Normativist methods were applied to assess current laws, a synthetic method to consolidate diverse information, and an analytical method to examine legislation and judicial cases in detail. Additionally, document reviews and interviews with trademark owners were included, providing a comprehensive view of the situation. The findings reveal that infringements often result from a lack of knowledge about the correct registration and use of trademarks, as well as intentional violations of intellectual property rights. While Ecuadorian legislation is theoretically consistent, it faces challenges in practical application, especially in terms of procedural speed. Strategies and recommendations were proposed to strengthen the legal protection of intellectual property in Ecuador. These include updating and clarifying laws, training authorities for more efficient enforcement, participating in international agreements, and using technologies to effectively detect and prevent infringements. The research underscores the urgent need to implement these measures to ensure a fair and respectful commercial environment for intellectual property, emphasizing the critical importance of protecting industrial property and distinctive signs for economic development and consumer confidence in Ecuador.